2020
DOI: 10.52434/jagros.v5i1.1107
|View full text |Cite
|
Sign up to set email alerts
|

Survei Perubahan Penggunaan Lahan Menggunakan Metode Unit Lahan Di Kecamatan Cibatu, Kabupaten Garut, Jawa Barat

Abstract: Perubahan penggunaan lahan merupakan fenomena yang banyak terjadi di berbagai tempat. Salah satu faktor pemicunya adalah adanya kebutuhan lahan. Kecamatan Cibatu merupakan bagian dari Kabupaten Garut dimana diduga terdapat kondisi perubahan penggunaan lahan. Penelitian dilakukan pada Bulan  September – November 2020 yang berlokasi di seluruh area Kecamatan Cibatu. Metode yang digunakan di dalam penelitian ini adalah metode analisis spasial dan metode survey. Metode analisis spasial yang digunakan adalah tumpan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Moreover, the changes in land use in 2012 and 2022 within the Jatibarang Reservoir can lead to increased erosion rates, sedimentation, and increased air discharge, which can disrupt the effectiveness of flood control infrastructure (reservoirs, dams, drainage channels, etc.). This is consistent with the findings of Swardana et al (2021) research, which suggests that changes in land use contribute to flooding due to reduced forest and plantation areas. To understand the spatial pattern of land use changes in the built-up areas from 2012 to 2022, the Nearest Neighbor Analysis (NNA) was conducted.…”
Section: Land Use Changessupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the changes in land use in 2012 and 2022 within the Jatibarang Reservoir can lead to increased erosion rates, sedimentation, and increased air discharge, which can disrupt the effectiveness of flood control infrastructure (reservoirs, dams, drainage channels, etc.). This is consistent with the findings of Swardana et al (2021) research, which suggests that changes in land use contribute to flooding due to reduced forest and plantation areas. To understand the spatial pattern of land use changes in the built-up areas from 2012 to 2022, the Nearest Neighbor Analysis (NNA) was conducted.…”
Section: Land Use Changessupporting
confidence: 92%
“…These environmental changes can have cascading effects on the reservoir's sustainability and the surrounding ecosystem. Previous studies, such as the research conducted by Dhanisworo (2022) and Swardana et al (2021), have reported similar environmental implications of land use changes, including increased erosion rates, sedimentation, and disruption of flood control infrastructure.…”
Section: Discussionmentioning
confidence: 70%